Pharmacological effects of higenamine based on signalling pathways and mechanism of action - Chen, De-ta; Rao, Wu; Shen, Xue; Chen, Lin; Wan, Zi-jian; Sheng, Xiao-ping; Fan, Tian-you (Frontiers in Pharmacology, 2022)
Higenamine (HG) is a chemical compound found in various plants, such as aconite. Recent pharmacological studies have demonstrated its effectiveness in the management of many diseases. Several mechanisms of action of HG have been proposed; however, they have not yet been classified. This review summarises the signalling pathways and pharmacological targets of HG, focusing on its potential as a naturally extracted drug. Articles related to the pharmacological effects, signalling pathways and pharmacological targets of HG were selected by searching the keyword ‘Higenamine’ in the PubMed, Web of Science and Google Scholar databases without limiting the search by publication years. HG possesses anti-oxidant, anti-apoptotic, anti-inflammatory, electrophysiology regulatory, anti-fibrotic and lipid-lowering activities. It is a structural analogue of catecholamines and possesses characteristics similar to those of adrenergic receptor ligands. It can modulate multiple targets, including anti-inflammation- and anti-apoptosis-related targets and some transcription factors, which directly or indirectly influence the disease course. Other naturally occurring compounds, such as cucurbitacin B (Cu B) and 6-gingerol (6-GR), can be combined with HG to enhance its anti-apoptotic activity. Although significant research progress has been made, follow-up pharmacological studies are required to determine the exact mechanism of action, new signalling pathways and targets of HG and the effects of using it in combination with other drugs.